Conceptual design of a system of RMP coils for the TCABR tokamak - Salvador, Felipe Machado (2022)
The high confinement mode observed in tokamak plasmas is seen as the most promising operational regime for economically viable nuclear fusion power plants. A particular characteristic of the high confinement plasmas is the onset of periodic instabilities known as edge localized modes (ELMs). These instabilities generate unacceptably large heat fluxes on the divertor plates that erode the divertor and reduces significantly its life time on a future reactor. Therefore, there is a need to develop ELM control methods in large machines, such as ITER. Several experiments have demonstrated that the application of non-axisymetric resonant magnetic perturbations (RMPs), created by electric currents flowing in localised coils outside the plasma, can be used to control ELMs. Due to its efficiency, ELM control coils, also called RMP coils, were added to ITER baseline project. Although the RMP coils have been successfully used to suppress ELMs in various tokamaks, the numerical modelling of these plasma discharges reveal that current physical models are not capable of describing satisfactorily the observed effects. The lack of a trustworthy physical model to describe the impact of RMP fields in tokamak plasmas is a central topic when plasma physics scientists try to predict the plasma reaction to the RMP fields in ITER. In order to enhance the numerical results reliability, carefully designed experiments to validate physical models are being realised in several tokamaks around the globe. Here in Brazil, a significant upgrade of the TCABR tokamak, operated at Plasma Physics Laboratory of Institute of Physics of the University of São Paulo, is in progress. In this upgrade, it is planned the installation of six sets of RMP coils, which enable the TCABR to test physical models used to predict the plasma response to RMP fields. This work has the objective of designing the RMP coil sets that will be installed in TCABR, which enables the validation of physical models in a wide variety of plasma scenarios, RMP field configurations and magnetic spectra with a large range of poloidal and toroidal harmonics.